2006
DOI: 10.1097/00004703-200612000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Social Behavior Problems in Boys with Duchenne Muscular Dystrophy

Abstract: Duchenne muscular dystrophy (DMD) is a chronic, progressive pediatric disease that affects both muscle and brain. The objectives of the study were to examine parent reported behavior in children with DMD, investigate the influence of chronic illness, intellectual ability and etiology on behavior, and determine whether a specific behavioral profile is associated with DMD. Parental ratings of boys with DMD (n = 181) on the Child Behavior Checklist behavior scales were examined and compared to reported findings o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0
14

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 46 publications
5
58
0
14
Order By: Relevance
“…Social behavior problems may occur earlier in children with DMD, who tend to have poor social and interpersonal behavior skills. [32] In this study, the scores of the SF and Social Relationships were correlated well with the functional status ratings of the MDFRS. Therefore, strategies for improving functional performance may yield improvements in their social Indicates statistical significance between young and oldest groups (p < 0.05).…”
Section: Quality Of Life Of Dmdsupporting
confidence: 56%
“…Social behavior problems may occur earlier in children with DMD, who tend to have poor social and interpersonal behavior skills. [32] In this study, the scores of the SF and Social Relationships were correlated well with the functional status ratings of the MDFRS. Therefore, strategies for improving functional performance may yield improvements in their social Indicates statistical significance between young and oldest groups (p < 0.05).…”
Section: Quality Of Life Of Dmdsupporting
confidence: 56%
“…47 Among the neurobehavioral concerns studied, higher frequencies of ADHD, 6,8,9 autism spectrum disorder, 8,1013 and obsessive-compulsive disorder (OCD) 8 have been reported for those affected with a dystrophinopathy compared to the general population. 8,11 Other studies have reported high levels of clinically significant externalizing and internalizing behaviors 11,1315 and difficulties with social functioning 11,1416 among affected individuals. These neurobehavioral and psychosocial concerns have been attributed, in part, to underlying neurocognitive deficits 17 and physical limitations that may arise with greater disease severity.…”
Section: Objectivementioning
confidence: 99%
“…Accordingly, the types of behavioral problems in children with motor disabilities also varied. The most reported problems are anxiety (Hendriks et al, 2001;Van Handel, Swaab, De Vries, & Jongmans, 2010), attention problems (Peters et al, 1999;Sigurdardottir et al, 2010), social problems (Hinton, Nereo, Fee, & Cyrulnik, 2006) and hyperactivity (Brossard-Racine et al, 2012;McDermott et al, 1996;Parkes et al, 2008). However, the use of different questionnaires hampers the comparability of studies addressing the prevalence of different types of problem behavior.…”
mentioning
confidence: 99%